Industri Keuangan Syari'ah Dalam Perspektif Manajemen Sumber Daya Insani - Purwana, Agung Eko (Justicia Islamica, 2009)
This study aims to analyze the Islamic finance industry from the perspective of human resource management, specifically related to the management of human resources in improving the operational effectiveness and performance of Islamic financial institutions. The method used is qualitative with a case study approach to several Islamic financial institutions in Indonesia. The results show that good human resource management, including recruitment, training, and employee development based on sharia principles, greatly affects service quality and customer satisfaction. In addition, challenges in managing SDI related to a deep understanding of sharia and a lack of competence in the managerial field are major obstacles in the development of this industry. This study recommends the need to increase the capacity of SDI in the sharia finance sector to create synergy between sharia principles and organizational goals.